Lectotypification of the Names of Two species of Omphalogramma (Primulaceae) - Husain, Danish; Katiyar, Pushpendra; Agnihotri, Priyanka; Husain, Tariq (Phytotaxa, 2016)
Members of the genus Omphalogramma Franchet (1898: 178) are perennial herbs with stout woody rhizomes bearing zygomorphic, solitary flowers. Confined to the Eastern Himalayas, approximately 13 species are known in the genus, of which nine are found in China (Hu and Kelso 1996).